A Chinese–Canadian Cross-Cultural Investigation of Transformational Leadership, Autonomous Motivation, and Collectivistic Value - Wang, Zheni; Gagné, Marylène (Journal of Leadership & Organizational Studies, 2013)
Synthesizing theories of transformational leadership and self-determination, this research investigated whether transformational leaders (a) promote the autonomous motivation of their subordinates and whether (b) it results in higher autonomous motivation when subordinates hold high collectivistic values. Multilevel data were obtained from work samples in China and Canada. The results showed a positive relation between managers’ transformational leadership and subordinates’ autonomous motivation cross-culturally. Although higher collectivistic values were related to higher autonomous motivation, collectivist values did not significantly moderate the motivational effect of transformational leadership.
Keywords: dept.mgt; peer-reviewed

Leadership, Generations and Small Business - Just, Renee (Scholars' Press, 2013)
Keywords: dept.mgt

Take charge: Understand control charts and know the difference in variation to better manage your people - Stepanovich, P.L.; Hopkins, P.J. (Quality Progress, 2013)
Keywords: dept.mgt; ⛔ No DOI found

Telling tales at work: an evolutionary explanation - Yang, Chulguen (Business Communication Quarterly, 2013)
This article explores the adaptive functions of storytelling in the workplace from an evolutionary perspective. Based on the analysis of ethnographic studies on hunter-gatherer and modern work organizations, this article claims that storytelling, as an adapted cognitive device, was selectively retained by natural and sexual selection, because of its survival and reproductive payoff. The narrative production through storytelling is a natural coping mechanism and has been functional in both old and new ways of working life under different ecological conditions. This article also highlights underlying adapted psychological mechanisms of storytelling and discusses some evolutionarily informed practical implications and pedagogical applications. © 2013 by the Association for Business Communication.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/047-449-660-219-354 tex.type: [object Object]
Keywords: dept.mgt; narrative; oral presentations; organizational communication